Lipoplex‐Functionalized Thin‐Film Surface Coating Based on Extracellular Matrix Components as Local Gene Delivery System to Control Osteogenic Stem Cell Differentiation. Issue 5 (29th November 2022) - Husteden, Catharina; Brito Barrera, Yazmin A.; Tegtmeyer, Sophia; Borges, João; Giselbrecht, Julia; Menzel, Matthias; Langner, Andreas; Mano, João F.; Schmelzer, Christian E. H.; Wölk, Christian; Groth, Thomas
Abstract: A gene‐activated surface coating is presented as a strategy to design smart biomaterials for bone tissue engineering. The thin‐film coating is based on polyelectrolyte multilayers composed of collagen I and chondroitin sulfate, two main biopolymers of the bone extracellular matrix, which are fabricated by layer‐by‐layer assembly. For further functionalization, DNA/lipid‐nanoparticles (lipoplexes) are incorporated into the multilayers. The polyelectrolyte multilayer fabrication and lipoplex deposition are analyzed by surface sensitive analytical methods that demonstrate successful thin‐film formation, fibrillar structuring of collagen, and homogenous embedding of lipoplexes. Culture of mesenchymal stem cells on the lipoplex functionalized multilayer results in excellent attachment and growth of them, and also, their ability to take up cargo like fluorescence‐labelled DNA from lipoplexes. The functionalization of the multilayer with lipoplexes encapsulating DNA encoding for transient expression of bone morphogenetic protein 2 induces osteogenic differentiation of mesenchymal stem cells, which is shown by mRNA quantification for osteogenic genes and histochemical staining. In summary, the novel gene‐functionalized and extracellular matrix mimicking multilayer composed of collagen I, chondroitin sulfate, and lipoplexes, represents a smart surface functionalization that holds great promise for tissue engineering constructs and implant coatings to promote regeneration of bone and other tissues. Abstract : An extracellular matrix‐inspired polyelectrolyte multilayer film is functionalized with lipoplexes and used as gene activated biomaterial surface coating for application in regenerative medicine. Collagen I‐chondroitin sulfate multilayers with embedded lipoplexes having plasmids encoding for bone morphogenic protein 2 gene promote adhesion and growth of mesenchymal stem cells and transfect them efficiently inducing their osteogenic differentiation.